فنون الطفل التفاعلية(الرقمية) - قريرة, حمزة; خمقاني, فائزة (جامعة الوادي - University of Eloued, 2021)
يعد أدب الطفل من حيث أجناسه غير مختلف عن أدب الكبار، ومن ناحية التصنيف فهو من أبرز التصنيفات الأدبية التي تخص فئة عمريّة مهمة في المجتمع، ونجده يضم القصة والمسرح والشعر وغيرها، ومن خلال تطوّر الوسائل التكنولوجية في المجال الرقمي حدثت ثورة على مستوى إنتاج النصوص الأدبية الموجهة للطفل وظهرت خطابات أخرى تعتمد على الوسائط المتعددة والعلامات غير اللغوية في خطابها للطفل، كالقصة المصورة، والفيديو .. معتمدة التقنيات الحاسوبية والبرمجيات المختلفة في الإنتاج أو التلقي الذي أصبح يتم عبر الوسيط الرقمي فقط، لتتطوّر الآدب الموجهة للطفل وتصبح فنونا متشعّبة، حيث تحتوي الجانب الأدبي بشقّه اللغوي، والجوانب غير اللغوية بوصفها أساسا في البناء. ومن خلال هذه الدراسة أحاول تتبّع هذه الفنون التفاعلية الرقمية الموجة للطفل، وتقديم عيّنة تجريبية خاصة في بناء قصة تفاعلية موجهة للطفل عبر مدونة الأدب والفن التفاعلي https://www.litartint.com Abstract: Child’s literature is amongst the important types of literature that is devoted to a certain vital age in the society. This literature is of no difference compared to mature peole’s literature; we can find that this type of literature has all literary genres like poetry, prose, drama, etc. Through the scale of time wherein new technological inventions has taken place, a revolution in literary productions was witnessed. To illustrate, Other types of multi-media based discourses and non-linguistic signs have come to appear in targeting the child like the storyboard, the videos, etc. Based on the computational techniques and various software in either production or reception that both have become to happen only via the digital medium; thus, child literature became rich a diverse with its linguistic and non-linguistic sides that are considered as basic conditions to start from. In this study, I try to track these digital interactive arts that are devoted to the child, and to give an empirical sample that is devoted specifically to children through the above link to a literature and interactive art blog. https://www.litartint.com
Child’s Interactive Arts (digital)
مقال
Keywords: طفل، مرحلة عمرية، أدب، روابط; child, age, Literatur , links